Childbearing women’s experiences of early pushing urge - Celesia, Monica; Nespoli, Antonella; Borrelli, Sara E. (Springer, 2016)
AIM: To explore childbearing women’s experiences of early pushing urge (EPU). STUDY DESIGN: A qualitative phenomenological study was undertaken in an Italian maternity hospital. The sample included 8 women that experienced EPU during labor. Data were collected through semi-structured interviews. FINDINGS: The findings are presented as three main themes: (a) women’s perceptions of EPU, (b) bodily sensations versus midwives’ advice: struggling between conflicting messages, and (c) the “a posteriori” feeling of women about midwives’ guidance during EPU. The perception of EPU was characterized by sense of obstruction, bone pain, and different intensity of pushing efforts when compared with those of the expulsive phase. Women found it difficult to follow the midwife’s suggestion to stop pushing because this contradicted their bodily sensations. However, the women recognized a posteriori the importance of the midwife’s support while experiencing EPU. Women appreciated the midwives’ presence and emotional support most of all because they seemed to be more concerned with the personal relationship they formed in labor rather than the usefulness or appropriateness of their advice. CONCLUSION: Midwives should consider women’s physical perceptions to help them cope with EPU, acknowledging that women may struggle when caregivers’ suggestions are in contrast to their physical perceptions. The women’s overall positive experiences of birth suggest that EPU might be considered as a physiological event during labor, reinforcing the hypotheses of previous research. The optimal response to the EPU phenomenon remains unclear and should be studied, considering EPU at different dilatation ranges and related clinical outcomes.